The reception of Walter Pater in Europe - Bann, Stephen (London ; New York : Thoemmes Continuum, 2004)
Just over a century after his death, Walter Pater''s critical reputation now stands as high as it has ever been. In the English-speaking world, this has involved recovery from the widespread neglect and indifference which attended his work in the first half of the twentieth century. In Europe, however, enthusiastic disciples such as Hugo von Hofmannsthal in the German-speaking world and Charles Du Bos in France, helped to fuel a growing awareness of his writings as central to the emergence of modernist literature. Translations of works like Imaginary Portraits, established his distinctive voic.
Series Editor's Preface; Acknowledgements; List of Contributors; List of Essays by Pater; Timeline: European Reception of Pater; Introduction; Italian; 1 'The sterile ascetic of beauty': Pater and the Italian fin de siècle; 2 The Fortune of The Renaissance in Italian Art Criticism, 1894-1944; 3 Pater's Reception in Italy: a General View; French; 4 'Influence occulte': the Reception of Pater's Works in France Before 1922; 5 'An untimely soul'? Pater's Academic Reception in France from the Early 1920s; German; 6 A German View of Pater.
Includes bibliographical references (pages 255-280) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Pater, Walter, -- 1839-1894 -- Appreciation -- Europe; Pater, Walter, -- 1839-1894 -- Translations -- History and criticism; Pater, Walter, -- 1839-1894 -- Influence; Pater, Walter, -- 1839-1894 -- Appréciation -- Europe; Pater, Walter, -- 1839-1894 -- Traductions -- Histoire et critique; Pater, Walter, -- 1839-1894 -- Influence; Pater, Walter, -- 1839-1894; Pater, Walter -- Schriftsteller; European literature -- English influences; Littérature européenne -- Influence anglaise; LITERARY COLLECTIONS -- Essays; Art appreciation; Influence (Literary, artistic, etc.); Translations; Europe; Rezeption; Europa; Receptie; Criticism, interpretation, etc